Imaging features of mycotic aortic aneurysms - Zhang, N.; Xiong, W.; Li, Y.; Mao, Q.; Xu, S.; Zhu, J.; Sun, Zhonghua; Sun, L. (AME Publishing Company, 2021)
Infectious aortitis (IA) is a rare and life-threatening cardiovascular disease. Early diagnosis and timely intervention are crucial for reducing mortality associated with mycotic aortic aneurysms (MAAs); however, early diagnosis is challenging due to the nonspecific symptoms. Some cases are diagnosed at an advanced stage or after developing complications, such as rupture or aortic fistula. Current state-of-theart imaging modalities—including computed tomography (CT), magnetic resonance imaging (MRI), and 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT—can detect infected aneurysms in clinically suspicious cases. MAA features on imaging include lobulated pseudoaneurysm, indistinct irregular arterial wall, perianeurysmal gas, perianeurysmal edema, perianeurysmal soft tissue mass, aneurysmal thrombosis, and high metabolic activity with increased uptake of FDG. Enlarged lymph nodes are often found adjacent to the aneurysm, while iliopsoas abscess (IPA), spondylitis, and aortic fistulas are commonly associated complications. After surgery or endovascular repair, radiological features—including ectopic gas, peri-graft fluid, thickening of adjacent bowel, pseudoaneurysm formed at the graft anastomosis, and increased uptake of FDG—may indicate an infection of aortic graft. This article provides an overview of the clinical and imaging features of MAAs. Thus, familiarity with the imaging appearances of MAAs may assist radiologists in the diagnosis and facilitation of timely treatment.